2022
DOI: 10.1108/caer-12-2021-0239
|View full text |Cite
|
Sign up to set email alerts
|

Impact of lockdown and government subsidies on rural households at early COVID-19 pandemic in China

Abstract: PurposeGiven the scarcity of data during the early stages of the COVID-19 pandemic in China, the decision-making for non-pharmaceutical policies was mostly based on insufficient evidence. The purpose of this study is to assess the effectiveness of these policies, such as lockdown and government subsidies, on rural households and identify policy implications for China and other countries in dealing with pandemics.Design/methodology/approachThe authors survey 2,408 rural households by telephone from 101 counties… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 41 publications
1
21
0
1
Order By: Relevance
“…Therefore, (1) Enterprises in various countries should make full use of the signaling role of digital transformation to enhance market recognition and commercial credit, broaden corporate financing channels to obtain financial support from governments, financial institutions, etc., thereby alleviating financing constraints, enhancing investment value, and reducing investment risks, in order to achieve the goal of enhancing stock liquidity [ 81 ]. Governments and institutions should fully understand the actual situation of digital transformation of domestic enterprises, formulate policies that are conducive to enterprise development, reduce administrative supervision constraints, provide subsidies for digital innovation and tax relief policies for enterprises, and act as credit guarantees for enterprises to help them expand financing channels [ 82 ]. This will offer guarantees for the digital transformation of enterprises and contribute to enhancing stock liquidity.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…Therefore, (1) Enterprises in various countries should make full use of the signaling role of digital transformation to enhance market recognition and commercial credit, broaden corporate financing channels to obtain financial support from governments, financial institutions, etc., thereby alleviating financing constraints, enhancing investment value, and reducing investment risks, in order to achieve the goal of enhancing stock liquidity [ 81 ]. Governments and institutions should fully understand the actual situation of digital transformation of domestic enterprises, formulate policies that are conducive to enterprise development, reduce administrative supervision constraints, provide subsidies for digital innovation and tax relief policies for enterprises, and act as credit guarantees for enterprises to help them expand financing channels [ 82 ]. This will offer guarantees for the digital transformation of enterprises and contribute to enhancing stock liquidity.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…The adverse shock on income and wealth to financial vulnerability consequently will impair the ability of the borrower to meet financial obligations. A study by Li et al (2022) empirically indicated that low-income households are more pessimistic as compared to high-income households. This is because low-income households are more economically vulnerable relative to the high-income households which are more resilient towards risks despite their losses.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…During COVID-19, most of the countries that were highly affected were in lockdown. Lockdown disrupts supply chains and logistics in rural areas, negatively impacting rural households' financial welfare [ 18 ]. The pandemic had a significant impact on the Chinese economy and the economies of the countries that were heavily affected.…”
Section: Introductionmentioning
confidence: 99%